Chimpanzee uses manipulative gaze cues to conceal and reveal information to foraging competitor. Issue 3 (27th November 2016) - Hall, Katie; Oram, Mike W.; Campbell, Matthew W.; Eppley, Timothy M.; Byrne, Richard W.; de Waal, Frans B.M.
Abstract : Tactical deception has been widely reported in primates on a functional basis, but details of behavioral mechanisms are usually unspecified. We tested a pair of chimpanzees ( Pan troglodytes ) in the informed forager paradigm, in which the subordinate saw the location of hidden food and the dominant did not. We employed cross‐correlations to examine temporal contingencies between chimpanzees' behavior: specifically how the direction of the subordinate's gaze and movement functioned to manipulate the dominant's searching behavior through two tactics, withholding, and misleading information. In Experiment 1, not only did the informed subordinate tend to stop walking toward a single high value food, but she also refrained from gazing toward it, thus, withholding potentially revealing cues from her searching competitor. In a second experiment, in which a moderate value food was hidden in addition to the high value food, whenever the subordinate alternated her gaze between the dominant and the moderate value food, she often paused walking for 5 s; this frequently recruited the dominant to the inferior food, functioning as a "decoy." The subordinate flexibly concealed and revealed gaze toward a goal, which suggests that not only can chimpanzees use visual cues to make predictions about behavior, but also that chimpanzees may understand that other individuals can exploit their gaze direction. These results substantiate descriptive reports of how chimpanzees use gaze to manipulate others, and to our knowledge are the first quantitative data to identify behavioral mechanisms of tactical deception. RESEARCH HIGHLIGHTS: Cross correlations show a subordinate chimpanzee tactically deceived a dominant by not gazing toward a valuable food (withholding), and recruiting to a "decoy" food (misleading). Chimpanzees understand that others can exploit their gaze direction.